2013
DOI: 10.1212/wnl.0b013e31827b90d1
|View full text |Cite
|
Sign up to set email alerts
|

Naturally occurring α-synuclein autoantibody levels are lower in patients with Parkinson disease

Abstract: Using a well-validated assay, we detected reduced α-Syn-nAbs levels in patients with PD compared to patients with AD and HC. The assay did not achieve criteria for use as a diagnostic tool to reliably distinguish PD from HC. Further studies are needed to assess α-Syn-nAbs as a biomarker in PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
101
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(111 citation statements)
references
References 31 publications
7
101
1
2
Order By: Relevance
“…Accordingly, we adopt the RP-HPLC step of Snca purification for all the studies reported here. The results we have obtained on the prevalence of anti-Snca antibodies in our case (iPD) and control (healthy subjects) study are in agreement with those published previously (Woulfe et al, 2002; Papachroni et al, 2007; Smith et al, 2012; Besong-Agbo et al, 2013) showing that there is no significant difference in the prevalence of anti-Snca antibodies between iPD patients and healthy controls. Furthermore, neither there is a higher prevalence of anti-Snca antibodies in non-manifesting (Asymp) or manifesting (Symp) LRRK2 carriers than in iPD patients or healthy controls when cut-off for anti-Snca positive reaction was established at OD ≥ 0.3 by endpoint ELISA and titer by immunoblot ≥1/100.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Accordingly, we adopt the RP-HPLC step of Snca purification for all the studies reported here. The results we have obtained on the prevalence of anti-Snca antibodies in our case (iPD) and control (healthy subjects) study are in agreement with those published previously (Woulfe et al, 2002; Papachroni et al, 2007; Smith et al, 2012; Besong-Agbo et al, 2013) showing that there is no significant difference in the prevalence of anti-Snca antibodies between iPD patients and healthy controls. Furthermore, neither there is a higher prevalence of anti-Snca antibodies in non-manifesting (Asymp) or manifesting (Symp) LRRK2 carriers than in iPD patients or healthy controls when cut-off for anti-Snca positive reaction was established at OD ≥ 0.3 by endpoint ELISA and titer by immunoblot ≥1/100.…”
Section: Discussionsupporting
confidence: 93%
“…Afterwards, multi-epitopic Snca antibodies were found in patients from families with uncharacterized familial forms of PD, but its frequency was not significantly higher in iPD patients with respect to healthy controls (Papachroni et al, 2007). Later studies have shown that there is no significant difference in the presence of anti-Snca antibodies between iPD patients and healthy controls (Smith et al, 2012; Besong-Agbo et al, 2013), while other studies found significant differences, with higher frequency in iPD patients (Yanamandra et al, 2011). Nevertheless, the human anti-Snca antibodies have been poorly characterized.…”
Section: Introductionmentioning
confidence: 97%
“…These specific antibodies have been detected in one study in approximately 50% of individuals with sporadic PD, 90% of individuals with familial PD, and 30% of control cases. 29 Although another study failed to confirm the finding, 30 a recent study examined autoantibodies to the monomeric form α-synuclein and found an increase in these antibodies in serum in PD. 31 There is, consequently, a need for further studies to better delineate the potential role for α-synuclein as a PD biomarker.…”
Section: α-Synuclein a Key Component In Pd Pathogenesismentioning
confidence: 99%
“…Similar to biomarker discovery efforts in AD, autoantibodies to established biomarkers of PD have also been reported with inconsistent results. Some studies claim an increase in α-synuclein autoantibodies in PD patients relative to controls, while others find decreased levels, or simply no differential expression between the two groups (Besong-Agbo et al, 2013;Papachroni et al, 2007;Smith, Schiess, Coffey, Klaver, & Loeffler, 2012;Yanamandra et al, 2011). Another study by Double et al (2009) found significantly higher titers of autoantibodies directed against melanin in the sera of PD patients in earlier stages of disease; however, no additional data validating this observation have been reported by this group or others since its publication (Double et al, 2009).…”
Section: Parkinson's Diseasementioning
confidence: 78%